The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.33448/rsd-v9i8.6403
|View full text |Cite
|
Sign up to set email alerts
|

Agentes químicos na produção de mudas de elevada qualidade de Schizolobium amazonicum

Abstract: Objetivou-se avaliar o crescimento e qualidade de mudas de Schizolobium amazonicum (Huber ex Ducke) sob tratamento pré-germinativo de semente e aplicação foliar de agentes químicos durante a formação. O experimento foi realizado realizados no laboratório de análises de sementes e casa de vegetação da Universidade Estadual de Mato Grosso do Sul/Unidade Universitária de Cassilândia-MS. Utilizou-se o delineamento inteiramente casualizado, em esquema fatorial 2x3, sendo constituído por dois tratamentos pré-germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The DQI is a vital parameter to assess seedling quality, being more important than variables such as height (Dickson et al 1960;Matos et al 2020). Another variable of great importance to be considered is the RDM; it was observed that the seedlings from the 42%/50% greenhouse, as well as those from the 30% screenhouse, had roots with high weight, which means that there was an investment in producing denser roots, a characteristic of rustic plants that can adapt and survive in an environment more easily than plants with more fragile roots with less dry matter (Carneiro 1995), in addition to expanding the absorption of nutrients and promoting growth and superior performance.…”
Section: Literature Citedmentioning
confidence: 99%
See 1 more Smart Citation
“…The DQI is a vital parameter to assess seedling quality, being more important than variables such as height (Dickson et al 1960;Matos et al 2020). Another variable of great importance to be considered is the RDM; it was observed that the seedlings from the 42%/50% greenhouse, as well as those from the 30% screenhouse, had roots with high weight, which means that there was an investment in producing denser roots, a characteristic of rustic plants that can adapt and survive in an environment more easily than plants with more fragile roots with less dry matter (Carneiro 1995), in addition to expanding the absorption of nutrients and promoting growth and superior performance.…”
Section: Literature Citedmentioning
confidence: 99%
“…The use of mirrors as reflective material on benches in cultivation provided better seedlings of baru (Dipteryx alata Vog. )(Costa et al 2020a); however, the use of aluminized screen (Aluminet ® ) did not increase their quality (da Costa et al 2020). Seedlings of rubber tree rootstock (Hevea brasiliensis), clone GT1, showed a robust root system and better-quality seedlings on benches with Aluminet ® reflective material (Costa et al 2021).…”
Section: Introductionmentioning
confidence: 99%